The Polish physiotherapists’ state of knowledge about the act on the profession of physiotherapist - Małgorzata Kulesa-Mrowiecka (Medycyna Pracy, 2021)
Background Work on the Act on the Profession of Physiotherapist had been conducted since the 1990s. However, it was not until October 2015 that the legal regulations were eventually introduced, following which physiotherapists gained professional independence and became a profession of public trust. The aim of the study was to assess the factors influencing the knowledge of these legal regulations among physiotherapists.